Well, water, rock: holy wells, mass rocks and reconciling identity in the Republic of Ireland - Crawford O'Brien, Suzanne J. (Material religion, 2008)
This paper explores the significance of holy wells and mass stones in Southwest Ireland, as expressions of competing narratives of meaning, identity, faith and history. Drawing on ethnographic interviews and participant observation, this essay argues that these places and the ritual activities that regularly occur there reflect and reconstruct contemporary Irish identities. In an era of rapid cultural change, these places comprise a tangible and experiential connection to Irish heritage and tradition. As reflected in interviews, conversations and published documents, these places are viewed as simultaneously embodying indigenous pre-Christian spiritualities as well as being locations of a distinctively Catholic faith. At the same time, they are important as secluded locations where Irish Catholic parishioners held mass during the colonial era of English oppression and as locations of popular religion, in contradistinction to orthodox Roman Catholicism. As such, holy wells and mass rocks demonstrate the ability of sacred places to integrate and reconcile complex and heterogeneous identities.